AB0391 Sustained Remission and Rate of Relapse after Withdrawal of Biologic or Non-Conventional DMARD in Patients with Rheumatoid Arthritis (RA). (15th July 2016) - Castillo-Ortiz, J.D.; Castaneda-Sanchez, J.J.; Ramirez-Gomez, A.; Sanchez-Gonzalez, J.M.; Ramos-Remus, C.
Abstract : Background: Rheumatoid arthritis (RA) treatment has changed considerably over the last decade with the introduction of biologics and target synthetic non-conventional DMARDs. In spite of algorithms about when to begin using these drugs, data about when to stop them are scant. Objectives: To assess the length of remission in patients with RA who had to discontinue a biological or a non-conventional DMARD because a clinical trial ended, and to compare survival remission curves. Methods: A prospective cohort study of RA patients assembled at the time of their last dose of any of the following drugs: tocilizumab subcutaneous (TCZ-SC), TCZ intravenous (TCZ-IV), or targeted synthetic oral drugs (tsDMARDs) tofacitnib or baricitinib p.o. All patients were in RA remission (DAS-28 <2.6 and absence of swollen joints). Patients were followed at our clinic in the following way: 1) each patient had a structured telephone interview based on the COPCORD questionnaire every eight weeks by a senior medical student; 2) each patient was instructed to communicate with our center immediately if they were experiencing swollen joints, and 3) All patients had in-office assessments with the same rheumatologists every four months. The primary outcome was RA relapse, defined as the time (months) when the patient presented at least one swollen joint. Survival remission curves were calculated per type of drug (TCZ vs. tsDMARDs) and per route of administration (PO, SC or IV). A Long Rank Test was used to assess differences among survival curves and p<0.05 was considered significant. A Cox analysis was used to assess baseline predictors for relapse times. Results: 99 patients were included, 88% female, with a mean age of 47±13 years. Sixty patients were treated with TCZ-IV, 18 with TCZ-SC and 21 with tsDMARDs-PO. Over the following 165 person-years, 27 (27%) remained in RA remission and 73% developed flare-ups (9 months was the median period for a flare-up). There were no significant differences among the three types of administration (IV, SC, and PO) or between the two classes of drugs (biological vs. tsDMARD). None of the baseline variables were significant as predictors of flare-ups. Conclusions: Long-term clinical remission is possible in a number of patients with RA after suspending a biological or non-conventional DMARD. This feature has also been reported with other biological agents, but not with tsDMARDs. Additional data are required to support recommendations for discontinuing a biological agent after achieving remission. Disclosure of Interest: None declared